Analisis Pengaruh Strategi Pemasaran City Branding, Word Of Mouth Terhadap Kepuasan Dan Loyalitas Wisatawan Kota Wisata Batu (Studi Kasus Pada Mahasiswa Malang) - Ronce Arum Melati; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract In the current era of globalization, there is intense competition between cities that is increasingly undeniable. This condition continues to occur today, cities in Indonesia are competing to find the best potential in order to increase their attractiveness. This situation requires each region to form a strong brand in facing global demands. Batu City in East Java is one of the cities that utilizes city branding marketing techniques to support city development. The city government under the leadership of mayor Eddy Rumpoko initiated a branding effort with one of its programs, namely the launch of the Kota Wisata Batu (KWB) tagline which was later changed to “Shining Batu” in 2013. The purpose of this study was to determine the effect of city branding marketing strategies on tourist satisfaction in Batu Tourism City, to determine the effect of city branding marketing strategies on tourist loyalty in Batu Tourism City, the impact of word-of-mouth marketing techniques on visitor satisfaction in Batu Tourism City, the impact of word-of-mouth marketing strategy on tourist loyalty in Batu Tourism City, and to determine the effect of tourist satisfaction on tourist loyalty in Batu Tourism City. The population in this study were students from the city of Malang who had visited Batu Tourism City. Purposive sampling, a methodology for gathering samples based on specific criteria utilizing a questionnaire distributed to 100 respondents and the SPSS analytic tool, is the non-probability sampling technique used by the approach method. The findings revealed that city branding has a significant impact on visitor satisfaction, word-of-mouth has a significant impact on visitor satisfaction, city branding has a significant impact on visitor loyalty, tourist satisfaction has a significant impact on visitor loyalty. Keywords: City Branding, Word Of Mouth, Tourist Satisfaction, Tourist Loyalty.